Web-Based Information System for Rental and Asset Data Collection on Wedding Organizer using Laravel Framework - Nuranisyah; Yulianto; Emil Riza Putra (Politeknik Pertanian Negeri Samarinda, 2022)
The background of this research is Alya's Bridal House which rents wedding packages offline (requires to come directly to the place to order), this is still less effective and efficient. This study also discusses asset data collection on the Wedding Organizer which can help facilitate ordering transactions, scheduling, and making it easier for admins to check available stock. The purpose of this research is to create a web-based rental information system and Asset Data Collection using the Laravel Framework programming language and MySQL as the database. The results of this study indicate that the trials generated on the respondent's test that the application used can facilitate asset data collection and optimize wedding package rental scheduling and can order wedding packages online properly.